Experimental study of the flow forces in the hydraulic poppet valve - Tyurebekov, Yermek (2010)
Poppet valve is a well-known valve and used in many industrial applications. To increase the efficiency of the poppet valve, the project had been carried out to study the flow forces acting on the hydraulic poppet valve. The hydraulic poppet valve is designed to allow flow in the forward position, and prevent the flow in backward position, with a spring attached to the poppet valve. The experiments is conducted under two vary conditions, which is to examine the flow force due to the increasing of pressure, and also due to the increasing of flow rate. The data is useful to study how the flow force can influence the height of the poppet valve lift, thus influence the efficiency of the poppet valve.